Staphylococcus aureus and MRSA Colonization Rates among Gravidas Admitted to Labor and Delivery: A Pilot Study - R. Beigi; J. Hanrahan (Hindawi Limited, 2007)
Objective. To determine colonization rates of Staphylococcus aureus given the potential for future intervention trials aimed at reducing surgical-site infectious morbidity, and to estimate methicillin-resistant Staphylococcus aureus (MRSA) rates in our patient population. Study design. Prospective pilot investigation comprising data from 104 gravidas admitted to an urban labor and delivery unit. All underwent anterior nares culture collection with a subset also undergoing vaginal culture collection. Results. Twenty-two percent of women were colonized in the anterior nares. Of the 28 women who had vaginal cultures collected, 4/28 (14.2%) demonstrated Staphylococcus aureus colonization. There was 82% concordance between the nares and vagina. Nine percent of isolates were MRSA strains. Overall, 2/96 (2.1%) of women were MRSA-colonized. Conclusions. Rates of Staphylococcus aureus colonization among gravidas entering labor and delivery are modest and consistent with the general population. MRSA rates among gravidas appear to be reassuringly low in this pilot study.